2020
DOI: 10.1186/s13326-020-00227-9
|View full text |Cite
|
Sign up to set email alerts
|

De-identifying free text of Japanese electronic health records

Abstract: Background Recently, more electronic data sources are becoming available in the healthcare domain. Electronic health records (EHRs), with their vast amounts of potentially available data, can greatly improve healthcare. Although EHR de-identification is necessary to protect personal information, automatic de-identification of Japanese language EHRs has not been studied sufficiently. This study was conducted to raise de-identification performance for Japanese EHRs through classic machine learning, deep learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In the UK, the majority of European countries, the US (23), China (24) and Japan (25) patient consent for research using de-identified routinely collected data, such as those within Schematic representation of the adaptive process when conducting research using retrospective data from Electronic Health Records. An iterative process is recommended between the preliminary stages of a study highlighted by the light grey square (reviewing the literature, formulating hypotheses, data exploration and conceptualising its relationships) and the later stages of developing analysis protocols, interpretations of results and final reports.…”
Section: Access and Ethical Approvalmentioning
confidence: 99%
“…In the UK, the majority of European countries, the US (23), China (24) and Japan (25) patient consent for research using de-identified routinely collected data, such as those within Schematic representation of the adaptive process when conducting research using retrospective data from Electronic Health Records. An iterative process is recommended between the preliminary stages of a study highlighted by the light grey square (reviewing the literature, formulating hypotheses, data exploration and conceptualising its relationships) and the later stages of developing analysis protocols, interpretations of results and final reports.…”
Section: Access and Ethical Approvalmentioning
confidence: 99%